Foshan Martial Arts Culture: Research on the dynamic balance between historical authenticity and modern adaptability in the inheritance of intangible cultural heritage - Fangjia Gu; Arkom Sangiamvibool (Environment and Social Psychology, 2025)
This study explores the historical evolution of Foshan martial arts culture and its contemporary multifaceted significance, analyzing its social status and challenges in cultural transmission. By examining the formation of community identity within Foshan martial arts communities, the research reveals the developmental trajectory of their collective consciousness. The study innovatively links Foshan martial arts’ cultural development with psychological identity, providing both theoretical insights and applied strategies for safeguarding and promoting intangible cultural heritage within the changing context of modern cultural adaptation.